Vacuolar H+ ATPase expression and activity is required for Rab27B‐dependent invasive growth and metastasis of breast cancer. Issue 4 (7th March 2013) - Hendrix, An; Sormunen, Raija; Westbroek, Wendy; Lambein, Kathleen; Denys, Hannelore; Sys, Gwen; Braems, Geert; Van den, Rudy; Cocquyt, Veronique; Gespach, Christian; Bracke, Marc; De, Olivier
<x xml:space="preserve">Abstract</x> The secretory Rab27B small GTPase promotes invasive growth and metastasis in estrogen receptor (ER) α‐positive breast cancer cells by orchestrating the peripheral targeting of vesicles secreting proinvasive growth regulators. Increased Rab27B expression is associated with poor prognosis in breast cancer patients. The molecular mechanisms of peripheral Rab27B secretory vesicle distribution are poorly understood. Mass spectrometry analysis on green fluorescent protein (GFP)‐Rab27B vesicles prepared from GFP‐Rab27B transfected MCF‐7 human breast cancer cells detected eight subunits of the vacuolar H(+)‐ATPase (V‐ATPase) and the presence of V0a1 and V0d1 subunits was confirmed by Western blot analysis. Reversible inhibition of V‐ATPase activity by bafilomycin A1 or transient silencing of V0a1 or V0d1 subunits demonstrated that V‐ATPase controls peripheral localization and size of Rab27B vesicles. V‐ATPase expression and activity further controls Rab27B‐induced collagen type I invasion, cell‐cycle progression and invasive growth in the chorioallantoic membrane assay. In agreement, Rab27B‐dependent extracellular heat shock protein90α release and matrix metalloprotease‐2 activation is markedly reduced by bafilomycin A1 and transient silencing of V0a1 and V0d1 subunits. Poor prognosis ERα‐positive primary breast tumors expressing high levels of Rab27B also expressed multiple V‐ATPase subunits and showed a strong cytoplasmic and peripheral V‐ATPase V1E expression. In conclusion, inhibiting V‐ATPase activity by interfering agents and drugs might be an effective strategy for blocking Rab27B‐dependent proinvasive secretory vesicle trafficking in ERα‐positive breast cancer patients.